The great American quilt revival - Bonesteel, Georgia; Bonesteel, Paul.; Gellert, Matthew; Bonesteel Films Inc. ([United States] : Bonesteel Films, 2005)
Through interviews with quilters, historians, and collectors, tells the story of how quilts went from being everyday household items to recognized works of art, worthy of being exhibited in museums and galleries. Quilters discuss their art and its emotional impact on culture.
Special features: interview with Georgia Bonesteel; Quilters Hall of Fame with comments by Joyce Gross; tour of the 2004 Honoree's Quilt Exhibit; tour of quilts from 2004 Hazel Carter Collection Exhibit; bonus interviews; the quilted car.
Cinematography and editing, Paul Bonesteel, Evan Schafer ; original music, Rayna Gellert, Steven Heller.
Narrator, Georgia Bonesteel.
DVD.
Keywords: Quilts -- United States; Quilting -- United States